Varicocele: Management and the continuing controversies - P S Agbo; I A Mungadi; H U Liman; M Oboirien (Sahel Medical Journal, 2010)
Varicoceles have long been associated with infertility. Despite this long history, there remains much controversy regarding their aetiology and management. The aim of this review is to present the most current information on the management of varicoceles and to highlight some of the management controversies: Association of varicocele with male infertility; Management of varicocele in adolescent; safety and effectiveness of varicocele embolization and management of subclinical varicoceles. It is hoped that this review study will stimulate further research into this condition in order to find a more common ground regarding its management.